PENGARUH TINGKAT PENDIDIKAN, PENDAPATAN PER KAPITA DAN PENGANGGURAN TERHADAP KEMISKINAN DI DKI JAKARTA - Darma Rika S.; Munawaroh Munawaroh; Dita Puruwita (Fakultas Ekonomi Universitas Negeri Jakarta, 2012)
ABSTRACTThis research was aimed at describing connections between education, income per capita and unemployment to poverty in Indonesia. In this research, the data were taken from Badan Pusat Statistik (BPS). The analysis use qualitative and quantitative. Qualitative analysis described in descriptive about education, income per capita, unemployment and poverty in Indonesia. The quantitative analysis used Ordinary Least Squares (OLS) with secondary data. The Regression of research results show that: (1) education has a negative influence to poverty and the effect statistically significant. (2) income per capita has a negative influence to poverty and the effect statistically significant. (3) unemployment has a positive influence to poverty and the effect statistically significant.